Television and the Children of Ethnic Minorities - Comstock, George; Cobbey, Robin E. (Journal of Communication, 1979)
The issues that are raised by ethnic status are not exclusive to ethnicity but represent circumstances much wider in occurrence that appear more often among ethnic minorities.
Keywords: 1-TV; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Télé